1995
DOI: 10.4319/lo.1995.40.4.0718
|View full text |Cite
|
Sign up to set email alerts
|

The 18O:16O of dissolved oxygen in rivers and lakes in the Amazon Basin: Determining the ratio of respiration to photosynthesis rates in freshwaters

Abstract: The concentration and I80 : I60 ratio of dissolved oxygen were measured for 23 rivers and lakes of the Amazon Basin during 1988, 1990, and 199 1. With only two exceptions, the rivers and lakes had dissolved oxygen concentrations that were at 20-90% of atmospheric saturation levels. The aI80 of the dissolved oxygen ranged from 15 to 30?& (vs. SMOW). The 6180 for the lakes were the lowest at 15-23o/oo. &I80 <24.2'?& (the atmospheric equilibrium value) are the result of photosynthetic oxygen input. The 6180 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
155
3
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(167 citation statements)
references
References 23 publications
8
155
3
1
Order By: Relevance
“…4) Guy et al 1993), and oxygen consumption by respiration, which fractionates by ,18% and thereby leaves the residual O 2 pool enriched in 18 O (e.g., Quay et al 1995;Wang and Veizer 2000). Under the (simplifying) assumption that both d 18 O DO and %O 2 are constant over time, the combination of both parameters has been used in freshwater systems to estimate the metabolic balance of the water column (Quay et al 1995;Wang and Veizer 2000), Application of this approach to our data from the Tana freshwater samples (salinity , 1.8) results in an estimated P : R ratio of 0.42 6 0.08 (n 5 9; one outlier removed), although it must be stressed here that the underlying assumption of steady-state conditions is unlikely to be valid for such a dynamic and biogeochemically active system, and application of this approach would ideally be based on diurnal patterns of %O 2 and d 18 O (Parker et al 2005). In estuaries, however, the application of d 18 O DO data for quantitative estimates of the aquatic metabolism is substantially more complicated.…”
Section: Discussionmentioning
confidence: 99%
“…4) Guy et al 1993), and oxygen consumption by respiration, which fractionates by ,18% and thereby leaves the residual O 2 pool enriched in 18 O (e.g., Quay et al 1995;Wang and Veizer 2000). Under the (simplifying) assumption that both d 18 O DO and %O 2 are constant over time, the combination of both parameters has been used in freshwater systems to estimate the metabolic balance of the water column (Quay et al 1995;Wang and Veizer 2000), Application of this approach to our data from the Tana freshwater samples (salinity , 1.8) results in an estimated P : R ratio of 0.42 6 0.08 (n 5 9; one outlier removed), although it must be stressed here that the underlying assumption of steady-state conditions is unlikely to be valid for such a dynamic and biogeochemically active system, and application of this approach would ideally be based on diurnal patterns of %O 2 and d 18 O (Parker et al 2005). In estuaries, however, the application of d 18 O DO data for quantitative estimates of the aquatic metabolism is substantially more complicated.…”
Section: Discussionmentioning
confidence: 99%
“…4-7) emanating from the Sacramento-San Joaquin Delta region deserve some attention, as the origin of the d 18 O NO 3 in marine systems is the subject of some recent debate (Casciotti et al 2002). Earlier studies showed that the oxygen atoms of NO 2 3 formed during the process of nitrification originate from both water and dissolved oxygen (Hollocher et al 1981;Andersson and Hooper 1983;Hollocher 1984 (Quay et al 1995;Brandes and Devol 1997). Thus, the contribution of dissolved O 2 atoms to NO 2 3 isotopic composition should be +24% or higher.…”
Section: Northern Sf Baymentioning
confidence: 99%
“…Dark respiration and respiratory fractionation of O 2 isotopes-Incubation bottles were filled with water from 3 m depth and incubated (24-96 h) in a thermostat at in situ temperature. In recent studies, Quay et al (1995) and Benner et al (1995) showed that changes in incubation bottle volumes did not influence respiration rate or isotopic fractionation. Thus, in the present study, we used 300-ml BOD bottles, from which duplicate samples were taken for isotopic measurements.…”
Section: O 2 Gross Production-hmentioning
confidence: 99%